Dermestes Linnaeus 1758 - Háva, Jiří; Herrmann, Andreas (Zenodo, 2021)
1. Dermestes Linnaeus, 1758 The genus is distributed worldwide and comprises 91 species in 4 subgenera (Háva 2015a, 2020). Dermestes (s. str.) Dermestesater DeGeer, 1774. ALAZCACOCTDEFLGALAMEMDMIMNNE NH NJ NV OK PA RI SC TX VA WA WI; COS Dermesteshaemorrhoidalis Küster, 1852. CAILKYMITX WI; COS Dermesteslardarius Linnaeus, 1758. AL AKAZARCACOCTDEFLGA HIIAIDILIN KSKYLAMEMDMAMI MNMOMSMT NCND NENHNJNMNV NYOHOKPARISCSDTN TX UT VA VT WV WI WY; COS Dermestesnidum Arrow, 1915. ALCACT DE* FLGAILIN MA* MNNMNYOH OKRITXVAWIWV Dermestes peruvianus Laporte de Castelnau, 1840. CT FL IN KS NY MA* WI; COS Dermestespulcher LeConte, 1854. IAILINKSNHNY OH* OK* PATXWI Dermestes reductus Kalík, 1952. AL MN ND Dermestessignatus LeConte, 1874. AKAZCACOIDILMAMONENMNVORWA Dermestes ( Dermestinus Zhantiev, 1976) Dermestescaninuscaninus Germar, 1824. ALAZ ARCACOCTDE FLGAHIIAILINKS KY LAMAMDME MI MNMOMSMT NC NDNE NH NJ NM NV NY OH OK PA RI SC SD TN TX UT VA VT WIWVWY Dermestescaninusmannerheimi LeConte, 1854. CAIDIN* NMORTXWA Dermestes carnivorus Fabricius, 1775. AL AZ CA CO CT FL HI TX; COS Dermestesfasciatus LeConte, 1854. AZCACOIAIDILKAMI MN* MTNENMNDOR SDUTWAWIWY Dermestes frischii Kugelann, 1792. AL AR AZ DE FL GA HI IA ID IL IN KS KY LA MA MDME MI MNMO MSMT NC ND NE NH NJNM NV NY OH OK OR PA RI SC SD TN TX UT VA VT WA WI WV WY; COS Dermestesmaculatus DeGeer, 1774. ALARCACOCTDEFLGAHIILIAIDINKSKYLA MA MDME MI MN MOMS MT NC ND NE NH NJ NM NV NYOH OK OR PARI SC SD TN TX UT VA VT WA WV WI; COS Dermestesmarmoratus Say, 1823. ALAZCACOCTIDIAKS MN* MSMTNENDNM NV OKORSC SDTX WA WYUT Dermestes rattus rattus LeConte, 1854. AL CA CO ID MT OH OR SD UT WA WI* WY Dermestes rattus tristis Fall, 1897. CA ID OR WA WY Dermestessardous Küster, 1846. CA; PAL Dermestestalpinus Escholtzin Mannerheim, 1843. ALAKAZCACOCTID MA* MN* MT NE* NHNY OH OR RI TX UT WA* WI WY Dermestesundulatus Brahm, 1790. CODEIDILINMA MEMN* NCNH NJNYORRI WA WI WV; HOL Dermestes ( incertae sedis ) † Dermestes tertiarius Wickham, 1912. CO (Oligocene: Florissant) Published as part of ...